[Edikt] (s.n., 1699)
Dotyczy nadużyć w zakresie handlu zbożowego.
Rkps na wykl.: ``Reglemente, edicte [...] Tomus Sextus 1818 [...] 1679 bis 1735''
Keywords: Prawodawstwo; Prusy; Handel; nadużycie prawa; Zboże